The Effect of Facilities, Patient Reception Procedures, and Nurse Communication on Inpatient Satisfaction at Sultan Imanuddin Hospital - Saripah Marlisaningsih; Agusta Dian Ellina; Agustin (Health and Technology Journal (HTechJ), 2025)
Patient satisfaction is a critical indicator of healthcare service quality and a key determinant of a hospital's performance and reputation. This study analyzed the factors influencing inpatient satisfaction at Sultan Imanuddin Hospital, a regional referral hospital in Central Kalimantan, Indonesia, focusing on three independent variables: facilities, patient admission procedures, and nurse communication. A quantitative research design was employed using a multiple linear regression analysis on data collected from 368 inpatients through a structured questionnaire. The data were analyzed using SPSS 25, incorporating validity and reliability tests, classical assumption tests, and hypothesis testing. The results revealed that facilities (β = 0.917, p = 0.000) and nurse communication (β = 0.382, p = 0.000) have a statistically significant positive effect on patient satisfaction. In contrast, patient admission procedures showed no significant influence (β = 0.004, p = 0.781). The Adjusted R-Square value of 0.979 indicates that the model can explain 97.9% of the variation in patient satisfaction, demonstrating a very high explanatory power. These findings suggest that physical infrastructure and interpersonal care are the most critical drivers of patient satisfaction in this setting. Therefore, hospital management should prioritize continuous improvement of facilities and invest in training programs to enhance nurses' communication skills. Although administrative procedures are essential, their impact on satisfaction is minimal, highlighting the need for a patient-centered approach emphasizing comfort, empathy, and effective interaction. This study contributes to the growing body of evidence on healthcare quality in public hospitals in Indonesia. It provides actionable insights for policymakers and healthcare managers aiming to improve service delivery and patient outcomes.